Workshop Penulisan Artikel Ilmiah untuk Publikasi Jurnal Nasional Terakreditasi Sinta di IAIN Kediri - Setiawan, Yayan Eryk (Jurnal Pengabdian UNDIKMA, 2021)
This service is in the form of a seminar that aims to provide understanding to students in writing accredited national scientific articles. This service activity was carried out at IAIN Kediri. This seminar activity consists of 4 activities, namely: presentation of material by the servant, review of scientific articles of one of the students by the servant, question and answer, and evaluation of community service. The results of the evaluation of this service activity show that the percentage of the questionnaire filling score is 86.6% which is in the high category which means that this workshop is very successful in providing understanding to participants in writing scientific articles. This success was due to good cooperation between the committee, presenters, and participants in participating in this workshop. Pengabdi recommends that so that students can write scientific articles, students must understand three knowledge, namely about: writing stages, writing scientific article components and submitting scientific articles to journals.